Theoretical Issues of Improving Communication Skills of Higher Education Students Based on Innovative Technologies and Interactive Methods - Atamuratova Munira Makhamadiyevna; Ramazanova Nazira Tulkunovna (Peerian Journals Publishing, 2022)
In this accelerating globe, the most optimal way to increase the effectiveness of general education is to organize lessons using interactive methods. So, what are interactive methods? What didactic possibilities do they have? What results can be guaranteed by the appropriate and purposeful use of interactive methods in the process of mother tongue education? We will try to answer these questions in this article.
Keywords: interactive; module system; innovative technology; interactivity